2010
DOI: 10.2478/abm-2010-0022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of effective-site target controlled infusion with standard bolus induction of propofol for laryngeal mask airway insertion

Abstract: Background:The laryngeal mask airway (LMA) is widely used in emergency medicine and surgical anesthesia. Several studies demonstrated induction of anesthesia with different plasma target-controlled infusion (TCI) of propofol for LMA insertion. However, there has been no study to compare the standard bolus propofol induction with the effective site TCI for LMA insertion. Objective: Compare the efficacy of induction of anesthesia with propofol for LMA insertion between the effective-site TCI, using 6 μg/mL, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies have shown that postoperative infection and tumor diffusion are closely related to the inhibitory effect of anesthesia on cellular immune function [9]. Some scholars have found that isoflurane inhalation promotes the proliferative and migratory abilities of tumor cells by upregulating the activity of tumor growth factors such as chemokine receptors [10]. In recent years, propofol, a popular drug used in radical operation of ovarian cancer, has attracted a lot of research interest with regard to its effect on the biological activities of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that postoperative infection and tumor diffusion are closely related to the inhibitory effect of anesthesia on cellular immune function [9]. Some scholars have found that isoflurane inhalation promotes the proliferative and migratory abilities of tumor cells by upregulating the activity of tumor growth factors such as chemokine receptors [10]. In recent years, propofol, a popular drug used in radical operation of ovarian cancer, has attracted a lot of research interest with regard to its effect on the biological activities of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Any kind of stimulus including the painting and draping by surgeon were avoided following insertion up to 5 min to minimize the interference with findings. The attempts at LMA insertion and Insertion Quality Score (IQS) as follows [2,6] and was noted by an investigator who was not further involved in the study.…”
Section: ~ 21 ~mentioning
confidence: 99%
“…Archie Brain devised supraglottic airway device (LMA) has revolutionized the anaesthetic procedures [1] . LMA insertion necessitates an optimum depth of anaesthesia to allow adequate relaxation of the jaw and prevention of reflexes of upper airway along with maintaining a cardio-respiratory equilibrium in a non-paralyzed patient [2] . Propofol as an induction agent for insertion of LMA has been widely used [2,3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target-controlled infusion (TCI) is widely used for generating propofol with a pharmacokinetic microprocessor. TCI offers improved hemodynamic stability and requires lower propofol doses when compared with manually controlled infusion (MCI) 2 . The anesthesiologist can also set the target-plasma or effectsite concentration of TCI to achieve the desired clinical effect 3,4 .…”
Section: Introductionmentioning
confidence: 99%